Prevalence and Molecular Analyses of Hemotrophic Mycoplasma spp. (Hemoplasmas) Detected in Sika Deer (Cervus nippon yesoensis) in Japan - TAGAWA, Michihito (The Japanese Society of Veterinary Science, 2013)
Hemotropic mycoplasmas (hemoplasmas) are cell-wall deficient, epierythrocytic bacteria that cause infectious anemia in several mammalian species. The prevalence of hemoplasma species was examined by screening and species-specific PCR using blood samples collected from 51 sika deer in Hokkaido, Japan. Molecular analyses were performed for the 16S rRNA, 23S rRNA and RNase P RNA (rnpB) gene sequences. A total of 23/51 (45%) deer DNA samples were positive for hemoplasmas in the screening PCR. Using species-specific PCR, 12 and 17 samples were positive for ‘Candidatus Mycoplasma haemocervae’ and ‘Candidatus M. erythrocervae’, respectively. Sequencing and phylogenetic trees of those three genes indicate that the ‘Candidatus M. haemocervae’ and ‘Candidatus M. erythrocervae’ detected in Japanese deer are potentially different species from the cervine hemoplasma found in deer from America and Brazil.